Loads and antimicrobial resistance of Campylobacter spp. on fresh chicken meat in Nueva Ecija, Philippines - F. B. Sison (2018)
This study was performed to determine the prevalence and to semiquantify Campylobacter spp. on chicken meat samples at 4 selected local wet markets in Nueva Ecija, Philippines, and to determine the antimicrobial resistance patterns of the Campylobacter isolates. Out of 120 chicken meat samples, 57 (47.5%) were Campylobacter spp. positive. The majority of isolated Campylobacter strains were identified as Campylobacter coli (54.4%) and 45.6% as Campylobacter jejuni. Most of these positive samples (52.6%) showed a very high quantitative Campylobacter contamination (most probable number > 2,400/g, lower confidence limit 580/g). For antimicrobial resistance testing, 44 C. coli/jejuni isolates were tested using the agar disk diffusion method. Out of these, 77.3% were resistant to ampicillin, followed by ciprofloxacin (70.4%), tetracycline (54.6%), erythromycin (20.2%), and gentamicin (11.4%). Of the isolates, 36.4% (n = 16) were resistant to 1 antimicrobial agent, 34.1% (n = 15) were resistance to 3 antimicrobial agents, 13.6% (n = 6) to 2 antimicrobial agents, 9.1% (n = 4) to 4 antimicrobial agents, and 6.8% (n = 3) to all 5 antimicrobial agents tested. Our data demonstrate a high contamination of fresh chicken meat with Campylobacter spp. at retail in the Philippines. The detected high Campylobacter prevalences and quantitative loads on chicken meat at retail in the Philippines highlight the need to implement efficient intervention measures along the food chain and to encourage sanitary handling of poultry meat. © 2014 Poultry Science Association Inc.